Plant parasitic nematodes associated with sugarcane in eastern Uttar Pradesh - RASHID, ABDUL (Indian Phytopathology, 2002)
Survey of nematode fauna associated with sugarcane at Kanoria Sugar and General Manufacturing Co. Ltd., Captainganj; Saraya Sugar Mills Ltd., Sardarnagar; Sugarcane Research Substation Kudaghat; Gorakhpur Khalilabad Sugar Mills Ltd., Khalilahad; Balrampur, Chini Mills Ltd., Balrampur; Tulsipur $ugar Mills Ltd., Tulsipur in 29 different location of eastern Uttar Pradesh revealed the occurrence of Tylenchorhynchus spp., Helicotylenchus spp., Pratylenchus spp., and Hoplolaimus sp in low (1-100/250 cc/soil) to high (501-1000 and >1000/250-cc/soil)population densities. Consistent association of Pratylenchus and prevalence of root-knot nematode, although in low numbers, is a matter of concern as these might build up to serious proportion with intensive cultivation of the crop. For productive cultivation of the crop it is therefore, desirable to monitor nematode population on a regular basis.